3D ordered porous MoxC (x = 1 or 2) for advanced hydrogen evolution and Li storage. Issue 21 (18th May 2017) - Yu, Hong; Fan, Haosen; Wang, Jiong; Zheng, Yun; Dai, Zhengfei; Lu, Yizhong; Kong, Junhua; Wang, Xin; Kim, Young Jin; Yan, Qingyu; Lee, Jong-Min
Abstract : By tuning the Mo to C ratios of 3D ordered porous Mo x C@C, superior hydrogen evolution and Li storage properties are achieved. Abstract : 3D ordered porous structures of Mo x C are prepared with different Mo to C ratios and tested for two possible promising applications: hydrogen evolution reaction (HER) through water splitting and lithium ion batteries (LIBs). Mo2 C and MoC with 3D periodic ordered structures are prepared with a similar process but different precursors. The 3D ordered porous MoC exhibits excellent cycling stability and rate performance as an anode material for LIBs. A discharge capacity of 450.9 mA h g −1 is maintained up to 3000 cycles at 10.0 A g −1 . The Mo2 C with a similar ordered porous structure shows impressive electrocatalytic activity for the HER in neutral, alkaline and acidic pH solutions. In particular, Mo2 C shows an onset potential of only 33 mV versus a reversible hydrogen electrode (RHE) and a Tafel slope of 42.5 mV dec −1 in a neutral aqueous solution (1.0 M phosphate buffer solution), which is approaching that of the commercial Pt/C catalyst.